Pathophysiology of Coagulopathy in Hematological Malignancies and in COVID-19. Issue 6 (1st June 2021) - Levi, Marcel
Abstract : Many severe illnesses with a systemic impact may cause activation of coagulation. While systemic activation of coagulation leads to a coagulopathy that follows many common activation pathways and failure of endogenous regulatory anticoagulant systems, underlying conditions may utilize distinctive pathogenetic routes and may vary in clinical manifestations of the coagulopathy. The coagulation derangement associated with hematological malignancies and the coagulopathy of coronavirus disease 2019 (COVID-19) clearly demonstrate such differences. Malignancies are associated with venous thromboembolism due to the biological effect of malignant cells, frequent medical interventions, or the presence of indwelling vascular catheters. The underlying pathogenesis of cancer-associated coagulopathy relies on tissue factor-mediated activation of coagulation, cytokine-controlled defective anticoagulant pathways, fibrinolytic changes, and dysfunctional endothelium. There is an additional risk caused by anti-cancer agents including chemotherapy and immunotherapy. The underlying pathogenetic factor that contributes to the thrombotic risk associated with chemotherapy is endothelial cell injury (or loss of protection of endothelial integrity, for example, by vascular endothelial growth factor inhibition). In addition, individual anti-cancer agents may have specific prothrombotic effects. One of the remarkable features of severe COVID-19 infections is a coagulopathy that mimics but is not identical to the disseminated intravascular coagulation and thrombotic microangiopathy and has been identified as a strong marker for an adverse outcome. Severe COVID-19 infections cause inflammation-induced changes in coagulation in combination with severe endothelial cell injury. This coagulopathy likely contributes to pulmonary microvascular thrombosis, bronchoalveolar fibrin deposition (which is a hallmark of acute respiratory distress syndrome) and venous thromboembolic complications.